(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
In this article it is argued that in the context of critical media and cultural studies’ emphasis onideology, the accent in understanding peace journalism frequently falls on peace journalismas advocacy journalism and on peace journalism as an ideological manipulation of therepresentation of war, conflict, terrorism, protest and violence. For an alternative understandingof peace journalism, and in the light of renewed academic interest in the understanding of worldand life view as a comprehensive set of values underlying cognition and representation, thisarticle suggests a focus on the description and analyses of the a priori values underlying ajournalist’s world and life view and demonstrates how such values may or may not be rooted ina fundamental world and life view predisposed to peace versus violence and war as a solutionto conflict. Given world and life view’s emphasis on meaning and meaning-making, the articlethen suggests an understanding of peace journalism and an understanding among journalistsof their work, as a semiotic act and as such signifying and representing the values of world andlife views in rhetorical and dialogical ways. Such an understanding and consciousness may leadto heightened journalistic sensitivity regarding how war, violence, conflict and hate are reported.This article deals in consecutive parts with the topics peace journalism, world and life view asa construct and its possible application in the field of peace journalism, and journalism as asemiotic act, characterised by signification, representation, rhetoric and dialogue as four of themain building blocks of journalistic communication, including peace journalism.